2019
DOI: 10.1093/cercor/bhy334
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Enhanced Memory for Meaningful Associations with Age

Abstract: Evidence suggests that age differences in associative memory are attenuated for associations that are consistent with prior knowledge. Such knowledge structures have traditionally been associated with the default network (DN), which also shows reduced modulation with age. In the present study, we investigated whether DN activity and connectivity patterns could account for this age-related effect. Younger and older adults underwent functional magnetic resonance imaging as they learned realistic and unrealistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…In one notable study, older adults showed greater default network activity and enhanced functional connectivity between default and control-network regions during retrieval of realistic versus unrealistic grocery-item prices using a subsequent memory paradigm. The authors interpreted these functional brain differences as evidence for greater reliance on stored memory representations for meaningful associations in older adults in contrast to greater reliance on controlled encoding and retrieval processes in young (Amer, Giovanello, Nichol, Hasher, and Grady, 2019).…”
Section: Decha: a Unified Account Of Cognitive And Brain Agingmentioning
confidence: 99%
“…In one notable study, older adults showed greater default network activity and enhanced functional connectivity between default and control-network regions during retrieval of realistic versus unrealistic grocery-item prices using a subsequent memory paradigm. The authors interpreted these functional brain differences as evidence for greater reliance on stored memory representations for meaningful associations in older adults in contrast to greater reliance on controlled encoding and retrieval processes in young (Amer, Giovanello, Nichol, Hasher, and Grady, 2019).…”
Section: Decha: a Unified Account Of Cognitive And Brain Agingmentioning
confidence: 99%
“…One possibility is a division of labor, such that prior knowledge biases the cortical memory system toward assimilation of novel information 16 , while shifting hippocampal processes to resolve interference 23 . Across rodents and humans, studies demonstrate that during new learning, prior knowledge enhances cortical activation and cortico-cortical functional connectivity, while also modulating hippocampal activation and functional connectivity with the cortex 11,18,19,[24][25][26][27][28][29][30][31][32][33][34] (for reviews, see refs. 16,35,36 ).…”
mentioning
confidence: 99%
“…Studies in aging populations support that resting network activity and connectivity patterns underlie enhancement of memory in older adults for meaningful associations [26]. It has also been shown that working memory (WM)-related brain activity is greater in older than in younger adults, while such cortical over-recruitment in advanced old age has been attributed to a compensatory mechanism [27].…”
Section: Improvement Of Memorymentioning
confidence: 99%